"Mind the Gap" in Reporting the Outdated Statistics - Babak Moazen; Farimah Rezaei; Masoud Lotfizadeh; Mohammad Darvishi; Farshad Farzadfar (Kerman University of Medical Sciences, 2014)
Close cooperation between researchers and policy-makers to find the specific health needs of communities, would lead to taking evidence-based decisions in addressing communities' health problems. Publication errors, like reporting outdated statistics are among the key factors that influence effectiveness of such decisions.